Becoming a mother in the 'new' social world in Australia during the first wave of the COVID-19 pandemic. (July 2021) - Sweet, Linda; Bradfield, Zoe; Vasilevski, Vidanka; Wynter, Karen; Hauck, Yvonne; Kuliukas, Lesley; Homer, Caroline S.E.; Szabo, Rebecca A.; Wilson, Alyce N.
Highlights: Becoming a mother is a social experience, and one of major adaptation. Public health restrictions due to the COVID-19 pandemic caused stress and anxiety for women. The physical distancing restrictions resulted in women having a solitary childbearing experience. The separation from family and friends heightened the need for alternate social support for women. Women became resourceful in finding ways for their support needs to be met. Abstract: Background: Substantial public health measures occurred in Australian society during the COVID-19 pandemic to reduce the risk of community transmission. Little was known about the impact of these changes on childbearing women. Aim: To describe childbearing women's experiences of becoming a mother during the COVID-19 pandemic in Australia. Methods: A qualitative exploratory design using semi-structured interviews was used. Women were recruited through social media and self-nominated to participate in an interview. Maximum variation sampling was used. A total of 27 interviews were conducted with women across Australia. Data were analysed thematically. Findings: The thematic analysis resulted in four primary themes and ten sub-themes. The themes were 'going it alone – having a baby was an isolating experience' ('receiving maternity care alone', 'dealing with government restrictions', and 'desiring social support'), 'advocating for self or others' ('seeking reliable information', 'valuing peersupport', and 'having to be resourceful'), 'finding a way through' ('a changed experience for all', 'managing stress and anxiety', 'requiring constant adjustments', and 'managing fear mongering'), and 'keeping safe'. Conclusion: Becoming a mother during the COVID-19 pandemic in Australia was a profound experience for the women. Following the public health initiatives which resulted in physical distancing restrictions, isolation, and the need to provide and receive social and peer support were common experiences. Whilst public health initiatives are implemented to keep people safe, the social and emotional toll on childbearing women should be considered by healthcare professionals. Childbearing women need to be safe but also require support and reassurance.